MANAJEMEN SUPERVISI KLINIS KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SMP - Niken Oktaviani (Manajer Pendididikan, 2015)
The purpose of this study was to describe the quality of the principal’s clinical supervision management in increasing the teaching professionalisme in Junior High School Karang Jaya. The subjects of this study is the principal, teachers and staffs of senior high school Karang Jaya. The results of this study showed that the clinical supervision has been done by the headmaster and the teachers but it has not based on the good procedure. Besides, the clinical supervision has a good effect for the teachers and all the staffs. All the method that has been done by the headmaster could increase the teaching abilities.Keyword: management, clinical supervision, teaching abilities